2019
DOI: 10.1542/peds.2018-2565
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion for PDA Closure in Preterm Infants: A Randomized Controlled Trial

Abstract: BACKGROUND AND OBJECTIVES: Thrombocytopenia is associated with late closure of patent ductus arteriosus (PDA). There are few studies evaluating platelet transfusions to treat PDA. We compared liberal platelet-transfusion criteria (to maintain a platelet count >100 000 per µL) versus standard criteria achieve earlier PDA closure among thrombocytopenic preterm neonates (<35 weeks’ gestation) with hemodynamically significant PDA (hs-PDA) presenting within the first 2 weeks of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…Blood pressure was measured on the third day after birth, after 72 hours when the PDA was closed; it was found that the blood pressure of premature newborns with peripheral arterial ischemia was significantly more likely to be in the 50th percentile or lower. This result confirmed that low blood pressure can cause vasospasms and thrombosis, and consequently peripheral arterial ischemia and skin necrosis [25]. Premature newborns commonly experience low blood pressure due to treatment of their conditions and surgery, and very premature newborns commonly experience shock in the early neonatal period.…”
Section: Discussionsupporting
confidence: 65%
“…Blood pressure was measured on the third day after birth, after 72 hours when the PDA was closed; it was found that the blood pressure of premature newborns with peripheral arterial ischemia was significantly more likely to be in the 50th percentile or lower. This result confirmed that low blood pressure can cause vasospasms and thrombosis, and consequently peripheral arterial ischemia and skin necrosis [25]. Premature newborns commonly experience low blood pressure due to treatment of their conditions and surgery, and very premature newborns commonly experience shock in the early neonatal period.…”
Section: Discussionsupporting
confidence: 65%
“…Recent randomized trials 40–42 have provided evidence that, in some settings, platelet transfusions cause harm rather than provide benefit. Not administering platelet transfusions in these settings would preserve platelet inventories for transfusion indications where benefits are more clearly established.…”
Section: Potential Solutions To Increase Platelet Availabilitymentioning
confidence: 99%
“…Similarly, thrombocytopenia on the first day of life was associated with delayed ductal closure and the risk of hsPDA on day 7 of life [21]. In this context, transfusions to maintain platelets counts at >100,000/µL did not improve the rate of or hasten PDA closure [22] and were also associated with an increased risk of IVH [22]. Moreover, lowering the transfusion threshold from 50,000 to 25,000 platelets/µL was found to reduce the rates of death and major bleeding in preterm newborns [23].…”
Section: Discussionmentioning
confidence: 99%